2012
DOI: 10.5539/ijbm.v7n13p85
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Marketing Performance Evaluation System for Notebook Distributors

Abstract: The hi-tech industry plays an important role in the industry structure of Taiwan as evidenced by the development of the information industry, with the notebook industry in the lead. The aim of this study is to develop a marketing performance evaluation model for Taiwanese notebook distributors. A total of 19 marketing performance evaluation indicators, including financial-perspective factors, customer-perspective factors, internal process factors, and innovation and learning factors are established based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…Quantitative methods have been suggested as a way to prioritize different criteria in multiple areas of research. For example, Chang et al , (2012) applied the analytic hierarchy process to compare the relative weights of quantitative criteria for measuring marketing performance. The cited authors found that marketing performance criteria could be selected through a sequential sorting of the entire list of indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quantitative methods have been suggested as a way to prioritize different criteria in multiple areas of research. For example, Chang et al , (2012) applied the analytic hierarchy process to compare the relative weights of quantitative criteria for measuring marketing performance. The cited authors found that marketing performance criteria could be selected through a sequential sorting of the entire list of indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marketing performance is a measure of achievement obtained from the overall marketing activity process of an organization (Chang et al, 2012). In addition, Best (2009: 66-67) argues that marketing performance is a market metric that records customer behavior, which in turn will be an indicator of financial performance.…”
Section: Marketing Performancementioning
confidence: 99%
“…In addition, the study of Grawe et al (2009) uses main measurements that combine financial and marketing-based performance measures, namely: sales volume growth, profit margin growth, market share growth, and overall competitive position. Meanwhile, Chang et al (2012) use marketing performance indicators, such as: financial perspective; customer perspective; internal processes; and innovation and learning.…”
Section: Marketing Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Gama, (2011) measures marketing performance by using the dimension of market share, service quality, customer satisfaction, customer loyalty and brand equity. Chang et al, (2012) measures marketing performance with four perspectives, namely: financial perspective, customer perspective, internal process perspective and the perspective of learning and innovation. While Saekoo et al, (2012) measures marketing performance by using dimension of sales, growth in market share and market development.…”
Section: Introductionmentioning
confidence: 99%